The Effectiveness of Stress Inoculation Training to Reduce Academic Stress in PGSD Students - Oktafianti, Sherly; Hasanah, Muhimmatul; Sholichah, Ima Fitri (Universitas Mercu Buana Yogyakarta, 2023)
This study aims to determine the effectiveness of Stress Inoculation Training (SIT) in reducing academic stress levels in PGSD students. This research uses a quasi-experimental quantitative approach with Nonequivalent Control Group Design. The subjects in this study consisted of 6 PGSD students who had moderate-severe levels of academic stress. Then the subjects were divided into 2 groups, namely 3 subjects in the experimental group and 3 subjects in the control group. The measuring instrument used in this study is the Student Life Stress Inventory (SLSI) scale developed by Gadzella (1991). The training module is based on the theoretical reference of Donald Meichenbaum (1979 & 1985) and research on Stress Inoculation Training by Suryanto and Alfian (2020). Hypothesis analysis using the Mann-Whitney test technique with the help of the SPSS 26.0 application for windows. The results of the analysis showed that after being given Stress Inoculation Training (SIT) in the experimental group, there was a significant difference in scores between the experimental group and the control group with a value of Z = -1.964 and p = 0.05. Thus, it can be said that there is an effectiveness of Stress Inoculation Training (SIT) to reduce academic stress in PGSD students.